Type 2 Diabetes Patients on Dual Oral Therapy: Does Glycemic Control Continue to Deteriorate in these Patients? - A, Sirajudeen S; K, Dhanapal C; K, Noodhu A; P, Daniel S; V, Venkatachalam V; A, Khaled M (Indian Journal of Pharmacy Practice)
Objectives: The objective of this retrospective analysis was to evaluate the glycemic control and cardiac parameters in patients with type 2 diabetes mellitus who were prescribed dual oral therapy after the failure of diet, exercise and metformin monotherapy. Methods: Type 2 diabetics patients who were added a second oral agent to the previous metformin monotherapy at least 3 months prior to the baseline visit were followed during June 2012 to June 2013. Data collected from the patient files included demographic characteristics, medical history, physical examination findings, diabetes related laboratory measurements and treatment recommendations in each visit. The patients were followed up in a scheduled manner every three months and the above data were recorded in each visit. Results: A total of 61 patients with a mean age of 54.8±10.7 years participated in the study. During the study, HbA1c declined in the first visit and then started to increase gradually. Only 32.8% of patients achieved HbA1c ≤7%. The fasting blood sugar escalated gradually from the baseline to the fourth visit and only 13.1% of patients achieved ≤110 mg/dl. There was no marked change in the blood pressure, body weight and BMI. There was insignificant reduction in the total cholesterol and triglyceride level and there was no marked change in LDL, HDL and VLDL. Conclusion: Our findings suggest that the progressive deterioration of HbA1c observed while patients were treated with dual oral therapy and highlights the importance of aggressive monitoring and prompt intervention to improve glycemic control in type 2 diabetes patients
Keywords: BMI; Body Weight; Fasting Blood Sugar; Glycemic Control; HbA1c; Type 2 diabetes mellitus